The Transmission of Local Wisdom Values in the Formation of Social Behavior in the Community of Bekonang Village, Sukoharjo Regency - Syahin Muhammad Alhadi; Masrukhi Masrukhi (Universitas Negeri Semarang, 2026)
A value holds profound meaning for a community. Such values are embedded in the everyday life of society and are subsequently passed down from generation to generation, although they are often unconsciously practiced by the community itself. Existing and prevailing values have been proven to shape social behaviors through intense positive social interactions and the involvement of various stakeholders. This study focuses on three main aspects: (1) exploring local wisdom values that exist within the community; (2) uncovering the process of value transmission that has been maintained across generations; and (3) analyzing community behavior through the existing values. This research employs a descriptive qualitative approach and utilizes observation, interviews, and documentation techniques to collect data, which are then condensed, presented, and concluded. The findings of this study indicate that: (1) the values practiced by artisans and the community accumulate into values of responsibility and care; (2) the process of value transmission involves families, coworkers, the surrounding community, community leaders, and religious leaders; and (3) these values are able to shape responsible behavior among artisans and a “relaxed” attitude among the community in general.